Making positive family memories together and improving quality-of-life through thick sociality and bonding at local community festivals and events. (December 2019) - Jepson, Allan; Stadler, Raphaela; Spencer, Neil
Abstract: Our study contributes to the current research on tourism and quality-of-life (QOL) by investigating Memorable Event Experiences (MEE), as a primary resource for familial bonding and memory creation. A mixed methods approach (focus groups and questionnaires) is used to explore the QOL indicators of: physical well-being, psychological/emotional well-being and relationships with family within the context of localised event experiences. Findings from this study are transferable across all aspects of the tourism system, they demonstrate that experiencing an event together as a family can facilitate collective memory creation, familial bonding, and create thick sociality or 'we-relationships' and can therefore enhance a family's QOL in the long term. Highlights: Our paper tests memorable event experiences (MEE) as a primary resource for familial bonding and memory creation. Uses a mixed method approach (focus groups and questionnaires) to explore the QOL indicators of; physical well-being, psychological/emotional well-being and relationships with family within the context of event experiences. Memorable event experience findings from our study are transferable across all aspects of the tourism system: Experiencing events together as a family can facilitate collective memory creation, familial bonding, and create thick sociality or 'we-relationships' and can therefore enhance a family's QOL in the long term.